Equilibrium with a Market of Permits - Gilles Rotillon; Pierre-André Jouvet; Philippe Michel (Fondazione Eni Enrico Mattei (FEEM), 2004)
In this paper we present the main results of three original studies on the equilibrium with a market of tradeable permits in a static framework. In first study, we have considered an international equilibrium of two countries which depend on the quantity of permits to each country. The allocation is efficient if and only if it is proportional to efficient labor. A redistribution in favor of the less developed country implies a redistribution to this country but leads to a dilemma with efficiency. In the second study, we analyze the consequences of the choice between giving free permits to firms and other possibilities. We show that for equalizing incomes of production factors with there marginal productivities, each factor should receive a quantity of free permits proportional to its contribution to production. In the third study, we consider the partial equilibrium of an industry where each firm is characterized by a parameter combining production efficiency and pollution effect. We define a theoretical indicator of environmental efficiency and we analyze its properties.
Keywords: D50; F02; F18; 330; Pollution permits; Capital allocation; International equilibrium; Factor income; Environmental efficiency; Emissionshandel; Faktorpreis; Allokation; Effizienz; Theorie; Emissionshandel